Percutaneous treatment of a huge patent ductus venosus and severe portal vein hypoplasia using a Figulla Flex II atrial septal defect occluder in a 2-year-old infant: a case report. Issue 12 (11th November 2021) - Kardos, Marek; Kitzmueller, Erwin; Olejnik, Peter; Michel-Behnke, Ina
Abstract: Background: Intra- or extrahepatic porto-caval shunts (PCSs) can account for multiorgan dysfunction with pulmonary arterial hypertension and portosystemic encephalopathy as the most serious consequences of bypass of the hepatic circulation. The ductus venosus (DV) represents a rare foetal PCS and might be persistently patent in newborns after birth. Treatment strategies include surgical ligation and percutaneous device closure. The degree of portal vein hypoplasia limits therapy making liver transplantation the only option in some of them. Case summary: In a newborn female patient a huge persistently patent DV, known already prenatally, resulted in severe secondary portal vein hypoplasia. She presented with hyperammonaemia, elevated liver enzymes, and pulmonary hypertension. With only diminutive portal venous branches and exceedingly high portal venous pressures during test-occlusion of the DV, shunt closure was not possible. At the age of 2 years more favourable portal venous pressures allowed transcatheter device closure with a nitinol atrial septal defect occlusion device. Pulmonary artery pressures and ammonia levels normalized after the procedure without any signs of portal hypertension. Discussion: The case highlights the importance of meticulous imaging using balloon occlusion angiography of PCSs like the DV, to search for intrahepatic portal veins. Moreover, portal vein pressure during test-occlusion can identify patients amenable for surgical or endovascular shunt closure. Occlusion devices licensed for other indications like atrial septal defect closure can be used safely in huge PCS vessels in a one-step or staged procedure. Optimal timing of the intervention should be tailored to the patient's needs